(3GdCSGS dYbGFO GdGcjGSs - (3GdbGSe Hf eMeO Hf Ydj, GdefUhQ HGddgs
(3ChdgG (B:s
(3GdMeO ddg GdPi adb GUHGM GdYbhd ai bdhH GYdGe JQHJg aGTYdgG SHMGfg HeUGHjM GdGfhGQ hHYO aEfg deG cGf Yde GdcdGe gh CLd GdYdhe bOQkG hGYXegG MXkG hGcHQgG NWQkG s
(3BNQgG (B:s
(3bdfG GdeQGO GdCYXe YfO Gddg SHMGfg hdjS cPdc GdG GdPjf TgO Gdgd HGjeGfge hMce HNGJge Je cJGH GdGSGS s
(3Vef eLehY , JQJjHgG (B: 1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs